Struggling with capital: Recovery after severe traumatic brain injury among working‐age individuals in Denmark - Anette L. Hindhede (Wiley, 2024)
Abstract Objective This study uses capital theory to investigate survivors' investments in their bodies and the resources they accumulate during their rehabilitation trajectory, and how these factors impact their perception of recovery from their impairments. Methods Qualitative interviews were conducted with 20 patients of working age and their relatives, with audio recordings transcribed verbatim. Data analysis utilized an abductive approach informed by Bourdieu's capital theory. Findings During the initial phases of rehabilitation (acute and subacute), survivors invest in their physical bodies and acquire physical capital. However, they encounter a range of complex barriers when attempting to convert this capital into the resources necessary for re‐entering the workforce or pursuing education. These difficulties are linked to the lack of specialized community services in the later phases of their rehabilitation trajectory. Discussion and Conclusion Present‐day Danish healthcare rehabilitation focuses on restoring physical function and recovering physical capital. However, comprehensive rehabilitation to enhance mental and cognitive abilities and increase levels of emotional capital, which is crucial for working‐age individuals, is inadequately addressed within community services. This results in unequal treatment and care, contradicting the stated goal of equality in the Danish healthcare system. Patient or Public Contribution This study incorporated the perspectives of 20 individuals who have survived severe traumatic brain injury, as well as their relatives, to gain insights into their experiences throughout the rehabilitation process, the resources they have accumulated and how these factors contribute to their sense of recovery.